Effects of dabai (Canarium odontophyllum Miq) fruit extract on biochemical parameters of obese diabetic rats - Mokiran, Nurul Nadirah (2014)
The number diabetes mellitus incident has exploded globally and elevating over the years. A lot of medications have been extensively introduced to treat the illness. However, synthetic drugs cannot promise the safety upon long term usage. Dabai (Canarium odontophyllum) is an indigenous fruit of Sarawak that is rich in nutritional value. The main objective of this study was to investigate the effect of dabai fruit extract on biochemical parameters of obese-diabetic (Ob-db) rats. At first, the pulp and peel of dabai fruit was defatted with petroleum ether and then extracted with 80% of ethanol (v/v). The solvent was then removed and the extract was lyophilized. The dabai fruit powder was re-dissolved in 80% of ethanol and its antioxidant capacity was analysed using three different assays; DPPH scavenging activity, β-carotene bleaching assay and oxygen radical absorbance capacity (ORAC) assay. Total phenolic (TPC) and total flavonoid (TFC) contents were measured using spectrophotometer. The phenolic compounds in dabai fruit extract were identified by using HPLC-DAD and confirmed by HPLC-ESI-MS. The quantity of identified phenolic compounds in dabai fruit extract were in the order of catechin>vanilic acid >apigenin>epicatechin>ferulic acid > ethyl gallate> 4-hydroxybenzoic acid. In-vivo study was performed to determine the effect of dabai fruit extract on obese-diabetic rats. Male Sprague dawley rats were fed with high-fat diet for three months and followed by the injection of 35 mg streptozotocin (STZ)/kg body weight (BW). Dabai extract with doses of 300 and 600 mg/kg BW were supplemented to the rats for 4 weeks. The parameters investigated in this study were glucose level, insulin level, lipid profile [total cholesterol (TC), low density lipoprotein-cholesterol (LDL-c), high density lipoprotein-cholesterol (HDL-c) and triglyceride (TGs)], antioxidant enzymes [glutathione peroxidase (GPx) and superoxide dismutase (SOD)] and endogenous total antioxidant status (TAS). The short term effect of dabai fruit extract on glucose level was also evaluated in oral glucose tolerance test (OGTT). The results of this study showed that dabai fruit extract with a concentration of 600 mg/kg BW possed the greatest hypoglycemic effect compared to 300 mg/kg BW by significantly reduced glucose level at min 60 to 90 in OGTT accompanied with a significant reduction in HOMA-IR value. Moreover, the extract (600 mg/kg BW) also showed the greatest improvement in lipid profile by significantly increased HDL-c level and reduced TC and LDL-c level. Other than that, supplementation of 600 mg/kg BW of dabai extract also significantly increased GPx level and slightly increased the endogenous total antioxidant status (TAS). However, no effect was observed on TGs and insulin level in both concentrations (300 and 600 mg/kg BW). In conclusion, this study suggests that supplementation of 600 mg/kg BW of dabai fruit extract showed anti-diabetic properties and protective effect against its complication by its hypocholesterolaemic properties, short term glucose-lowering effect and improved the insulin resistance and antioxidant status. The bioactive compounds in dabai extract might be the one that responsible to improve the disturbance carbohydrate, protein and lipid metabolism in diabetes mellitus.